Contribution of RNA/DNA Binding Protein Dysfunction in Oligodendrocytes in the Pathogenesis of the Amyotrophic Lateral Sclerosis/Frontotemporal Lobar Degeneration Spectrum Diseases - Valori, Chiara F.; Neumann, Manuela (Frontiers in Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are two incurable neurodegenerative disorders, often considered as the extreme manifestations of a disease spectrum, as they share similar pathomechanisms. In support of this, pathological aggregation of the RNA/DNA binding proteins trans-activation response element DNA-binding protein 43 (TDP-43) or fused in sarcoma (FUS) is the pathological hallmark found in neurons and glial cells of subsets of patients affected by either condition (i.e., ALS/FTLD—TDP-43 or ALS/FTLD—FUS, respectively). Among glia, oligodendrocytes are the most abundant population, designated to ensheath the axons with myelin and to provide them with metabolic and trophic support. In this minireview, we recapitulate the neuropathological evidence for oligodendroglia impairment in ALS/FTLD. We then debate how TDP-43 and FUS target oligodendrocyte transcripts, thereby controlling their homeostatic abilities toward the axons. Finally, we discuss cellular and animal models aimed at investigating the functional consequences of manipulating TDP-43 and FUS in oligodendrocytes in vivo. Taken together, current data provide increasing evidence for an important role of TDP-43 and FUS-mediated oligodendroglia dysfunction in the pathogenesis of ALS/FTLD. Thus, targeting disrupted oligodendroglial functions may represent a new treatment approach for these conditions.